State dependent regional pole assignment controller design for a 3-DOF helicopter model - Arıcan, Ahmet Çağrı; Çopur, Engin Hasan; Inalhan, Gokhan; Salamci, Metin U. (Institute of Electrical and Electronics Engineers (IEEE), 2023)
For linear systems, a state feedback control law can be easily designed to keep all closed-loop poles inside a specified disk since the locations of the poles are unique. However, its application to nonlinear systems is not so simple. Therefore, this paper introduces a new pole placement method, named as State Dependent Regional Pole Assignment, for nonlinear systems. This proposed method produces a state dependent feedback control law, enabling the eigenvalues of the closed-loop matrix to be placed in a specified disk to achieve the desired control performance characteristics. The effectiveness of the method is tested on the 3 DOF Helicopter experimental setup. To verify its effectiveness, the experimental results of the nonlinear method are compared with those of the linear method.